SISTEM PAKAR DIAGNOSA KERUSAKAN HARDWARE KOMPUTER MENGGUNAKAN METODE CASE BASED REASONING PADA MOZZA COMPUTER - Hidayat, Taufik; Sapri, Sapri; Supardi, Reno (Jurnal Media Infotama, 2023)
Abstract: Mozza Computer is a computer shop that sells computers, printers, computer spare parts, computer accessories and provides computer and printer services. So far, the service process has been carried out by consumers coming directly to Mozza Computer with computers or printers that are having problems, then the service division will first check whether the device can be worked on directly or not. This requires quite a long time because consumers who come must queue because of limited employees to check for damage to the computer. An expert system for diagnosing computer hardware damage using the Case Based Reasoning Method on Mozza Computer was made to serve as a tool in making it easier to find out damage to computer hardware through an expert system application. In the process of identifying hardware damage, an analysis of the latest data will be carried out with case data that has occurred for a long time to obtain a percentage level of confidence in the damage. Based on the results of the tests that have been carried out, the functionality of the expert system for diagnosing computer hardware damage using the Case Based Reasoning Method on Mozza Computer has gone well as expected and is able to provide information on the results of consulting computer hardware damage